2021
DOI: 10.1590/s1678-9946202163073
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis associated with multibacillary polychemotherapy for leprosy

Abstract: Acute pancreatitis (AP) is an inflammatory disease associated with abdominal pain and elevated serum pancreatic enzymes. The most common etiologies are gallstones and alcoholism. Drug-induced AP is quite rare, lacks a solid understanding and has been occasionally reported. The diagnosis requires a great suspicion and a careful exclusion of other causes. We present a case of a 37-year-old man, previously diagnosed with leprosy that developed acute pancreatitis after starting the multibacillary polychemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Similarly, Van et al 11 in their study revealed that the levels of inflammatory factors in patients were upwardly increased with the increase of inflammatory response and positively correlated with the severity of the disease. PCT levels were considered to be positively correlated with AP severity by Zhang et al 12 and were found to have predictive value for complications of AP in a study by Maciel et al 13 as well, which is broadly consistent with our study. Pancreatic blood circulation disorders are now recognized as an important link in the development of severe pancreatitis.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Van et al 11 in their study revealed that the levels of inflammatory factors in patients were upwardly increased with the increase of inflammatory response and positively correlated with the severity of the disease. PCT levels were considered to be positively correlated with AP severity by Zhang et al 12 and were found to have predictive value for complications of AP in a study by Maciel et al 13 as well, which is broadly consistent with our study. Pancreatic blood circulation disorders are now recognized as an important link in the development of severe pancreatitis.…”
Section: Discussionsupporting
confidence: 92%